2022
DOI: 10.1002/hep4.2015
|View full text |Cite
|
Sign up to set email alerts
|

Elevated liver enzymes predict morbidity and mortality despite antiviral cure in patients with chronic hepatitis C: Data from the German Hepatitis C‐Registry

Frank Tacke,
Hartwig Klinker,
Klaus H. W. Boeker
et al.

Abstract: While direct‐acting antivirals (DAAs) cure chronic hepatitis C virus (HCV) infection in almost all patients, some patients remain at risk of liver disease despite HCV cure. In order to identify risk factors indicating liver‐related morbidity and death after viral cure, we included 6982 patients from the national multicenter real‐world German Hepatitis C Registry with regular follow‐up visits for up to 7 years after DAA therapy. Definitions for normal liver function tests (in women/men) were alanine aminotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…NASH determines asymptomatic elevation of ALT and AST levels in up to 90% of cases, once other liver disease causes are excluded [28]. Numerous studies have shown that serum levels of ALT and AST are elevated in CHC patients in different stages of the disease [29,30]. In this study, AST and ALT levels were significantly higher in all liver disease groups in comparison with CG.…”
Section: Discussionmentioning
confidence: 43%
“…NASH determines asymptomatic elevation of ALT and AST levels in up to 90% of cases, once other liver disease causes are excluded [28]. Numerous studies have shown that serum levels of ALT and AST are elevated in CHC patients in different stages of the disease [29,30]. In this study, AST and ALT levels were significantly higher in all liver disease groups in comparison with CG.…”
Section: Discussionmentioning
confidence: 43%
“…Considering the new era of CHC therapy via Direct-Acting antivirals(DAAs), DAAs are associated with > 95% cure rate and reduction in risk of developing HCC and are significantly beneficial in reducing diabetes mellitus, the levels of liver enzymes (GOT, GPT, and GGT) [ 33 , 35 ], and the severity of fatty liver disease[ 36 ]. Hence, eradication of CHC through DAAs therapy may prevent adverse outcomes of cirrhosis and HCC and is potentially beneficial for the regression of fatty liver and control of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings showed the importance for the combination of three factors including gender, FIB-4 index, and GGT. Furthermore, the present results suggested the importance of GGT as one of metabolic surrogate markers, including metabolic disorder, alcohol consumption, and fatty liver disease [ 11 ]. Recently, an international expert panel proposed a new definition of fatty liver, metabolic dysfunction-associated fatty liver (MAFLD).…”
Section: Discussionmentioning
confidence: 99%